2018
DOI: 10.1016/j.jshs.2017.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 3 months of full-court and half-court street basketball training on health profile in untrained men

Abstract: PurposeThe aim of the present study was to investigate whether street basketball organized as 3 v 3 on either a half court (HC) with 1 basket or a full court (FC) with 2 baskets could improve fitness and health profiles of untrained men after 3 months of supervised training.MethodsThirty-five untrained men (aged 20–42 years) completed the pre- and post-intervention testing (FC: n = 13, HC: n = 12, CO (control): n = 10). The training attendance was 2.0 ± 0.4 and 1.9 ± 0.3 times per week in FC and HC, respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
48
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 37 publications
(71 citation statements)
references
References 38 publications
16
48
7
Order By: Relevance
“… 31 Indeed, soccer players who had been retired for 15 years had a residual BMD benefit that was about half that found in active soccer players, whereas football players retired for over 35 years had no significant residual benefit in BMD. Consequently, to preserve the large gains in bone mineralization observed in FTY and FTE, continuation of lifelong regular high-impact exercise such as football, basketball, 51 and team handball 52 training appears to be necessary.…”
Section: Discussionmentioning
confidence: 99%
“… 31 Indeed, soccer players who had been retired for 15 years had a residual BMD benefit that was about half that found in active soccer players, whereas football players retired for over 35 years had no significant residual benefit in BMD. Consequently, to preserve the large gains in bone mineralization observed in FTY and FTE, continuation of lifelong regular high-impact exercise such as football, basketball, 51 and team handball 52 training appears to be necessary.…”
Section: Discussionmentioning
confidence: 99%
“…In the past decade, a number of studies have shown that soccer training organized as small-sided games led to a broad spectrum of positive health outcomes in both young and older adults, 12 as well as in people with lifestyle diseases. 13 , 14 , 15 , 16 , 17 , 18 Recently, other team games such as team handball, 19 basketball, 20 and floorball 21 , 22 have been shown to demonstrate positive health effects on untrained young women, post-menopausal women and middle-aged men. Vorup et al.…”
Section: Introductionmentioning
confidence: 99%
“…A recent editorial focused on the beneficial effects on fitness, health, motivation and social life provided by team sports [60]. Three studies from the University of Southern Denmark and the University of Copenhagen were examined: one related to small-sides team handball for women, one focused on basketball (both full-and half-court) and the latter focused on European football (soccer) and its possible lifelong benefits [61][62][63]. The results of these studies evidenced that: women who played handball showed an improvement in endurance and bone mineral density when compared to a sedentary control group, together with strong motivational and social scores; older players showed greater bone mineral density than non-active age-matched controls and, surprisingly, even compared to sedentary young men, demonstrating the benefits of lifelong physical activity.…”
Section: Football and Healthmentioning
confidence: 99%